Experimental and Numerical Investigation on the Impact of Emergent Vegetation on the Hyporheic Exchange - Huang, S. H.; Nuli, R.; Kang, P. K.; Shen, L.; Yang, J. Q. (Water resources research, 2025)
Hyporheic exchange leads to the transfer of gases, solutes, and fine particles across the sediment‐water interface, playing a critical role in biogeochemical cycles and pollutant transport in aquatic environments. While in‐channel vegetation has been recognized to enhance hyporheic exchange, the mechanisms remain poorly understood. Here, we investigated how an emergent vegetation canopy impacts hyporheic exchange using refractive index‐matched flume experiments and coupled numerical simulations. Our results show that at the same mean surface flow velocity, vegetation increases the hyporheic exchange velocity by four times compared to the non‐vegetated channel. However, the hyporheic exchange velocity does not increase further with increasing vegetation density. In addition, our results show that the hyporheic exchange velocity scales with the square root of sediment permeability. Our findings provide a predictive framework for hyporheic exchange in vegetated channels with varying vegetation densities and sediment permeabilities and could guide the future design of environmental management and restoration projects using vegetation. Plain Language Summary Aquatic vegetation is known to increase hyporheic exchange, which facilitates the exchange of gases, solutes, and fine particles between surface water and pore fluids within the sediment beds. Due to its ability to regulate the fate of pollutants, vegetation has been used to remediate contamination in many riverine and coastal restoration projects. However, the mechanisms through which vegetation enhances hyporheic exchange remain poorly understood, making it challenging for engineers to design effective restoration projects. In this study, we investigated how an emergent vegetation canopy impacts hyporheic exchange using both laboratory experiments and numerical simulations. Our results showed that at the same mean surface flow velocity, hyporheic exchange was four times faster in the vegetated channel than in a channel without vegetation. However, further increases in vegetation density did not enhance hyporheic exchange. Moreover, our results show that the hyporheic exchange velocity scaled with the square root of the sediment permeability. These findings provide theoretical guidance for engineers to estimate the hyporheic exchange rate in a vegetated channel and design effective restoration projects using aquatic vegetation. Key Points Index‐match experiments and coupled numerical simulations reveal detailed vertical flow paths around vegetation stems Stem‐scale vertical flow and canopy‐scale subsurface flow govern hyporheic exchange, as confirmed by experimental and numerical analyses Hyporheic exchange rate increased four times in a vegetated channel compared to a bare channel but did not increase with vegetation density